Shining a light on Auckland’s volcanic monster under the bed - Hopkins, Jenni (New Zealand Science Review, 2017)
If you asked a person to draw a volcano, generally they would draw a triangle shape, not unlike Mt Taranaki, with either steam coming out of the top, or lava flowing down the sides. What they would not draw is lots of little apparent hills and lakes, but this is what Auckland’s volcanoes are like. The Auckland volcanic field (AVF) is made up of lots of individual volcanoes that generally only erupt once, and are hence called ‘monogenetic’. Globally, monogenetic volcanic fields are poorly understood, and whilst these little single eruptions may seem less threatening to human life than a large imposing volcano like Mt Ruapehu or Mt Taranaki, the frightening thing is that the location of the next eruption is completely unknown. When you couple this unknown with a large urban population and nationally dependent infrastructure, the potential threat to humans of a future eruption dramatically increases. In order to reduce the unknowns, reconstructing the past eruptive history of the entire field can allow patterns or trends in eruptions to be uncovered, and allow better-informed predictions about a future eruption to be made.